Studies in mucorales : piptocephalidaceae - B.J. PATIL, M.S. PATIL and (Indian Phytopathology, 2002)
Present paper deals with 9 taxa belonging to the genus Syncephalis van Tieghem and L. Monnier (8 species and 1 var.) of the family Piptocephalidaceae. Out of these 9 taxa, 4 are new species, one is a new variety, 3 species have been recorded for the first time in India and one species viz. S. nodosa van Tieghem is new to the Maharashtra State, in which only perfect state has been recorded.